Burden of disease of type 2 diabetes mellitus: cost of illness and quality of life estimated using the Maastricht Study. Issue 10 (18th March 2020) - Janssen, L. M. M.; Hiligsmann, M.; Elissen, A. M. J.; Joore, M. A.; Schaper, N. C.; Bosma, J. H. A.; Stehouwer, C. D. A.; Sep, S. J. S.; Koster, A.; Schram, M. T.; Evers, S. M. A. A.
Abstract: Aims: To estimate the societal costs and quality of life of people with type 2 diabetes and to compare these results with those of people with normal glucose tolerance or prediabetes. Methods: Data from 2915 individuals from the population‐based Maastricht Study were included. Costs were assessed through a resource‐use questionnaire completed by the participants; cost prices were based on Dutch costing guidelines. Quality of life was expressed in utilities using the Dutch EuroQol 5D‐3L questionnaire and the SF‐36 health survey. Based on normal fasting glucose and 2‐h plasma glucose values, participants were classified into three groups: normal glucose tolerance ( n  = 1701); prediabetes ( n  = 446); or type 2 diabetes ( n  = 768). Results: Participants with type 2 diabetes had on average 2.2 times higher societal costs than those with normal glucose tolerance (€3, 006 and €1, 377 per 6 months, respectively) and had lower utilities (0.77 and 0.81, respectively). No significant differences were found between participants with normal glucose tolerance and those with prediabetes. Subgroup analyses showed that higher age, being female and having two or more diabetes‐related complications resulted in higher costs ( P  < 0.05) and lower utilities. Conclusions: This study showed that people with type 2 diabetes have substantially higher societal costs and lower quality of life than people with normal glucose tolerance. The results provide important input for future model‐based economic evaluations and for policy decision‐making. What's new?: The high costs of type 2 diabetes, together with its impact on quality of life, place a great burden on both the individual affected and society as a whole. People with type 2 diabetes have, on average, 2.2 times higher societal costs and experience a lower quality of life than people without type 2 diabetes. The total societal costs for people with ≥2 diabetes complications are 4.4 times higher than total societal costs for people without complications.